Response and progression in recurrent malignant glioma. - Hess, K. R. (1999)
In this article we report the results of a study of the relationship between response and progression in 375 patients with recurrent glioma enrolled in phase II chemotherapy trials. We reviewed the records of patients from 8 consecutive phase II trials, including 225 patients with recurrent glioblastoma multiforme and 150 with recurrent anaplastic astrocytoma. Median age was 45 years (range, 15-82) and median Karnofsky performance score was 80 (range, 60-100). Forty-one patients (11%) had more than two prior resections and/or more than two prior chemotherapy regimens. Best response was complete (n = 1) or partial (n = 33) in 34 patients (9%). Median time to response was 14 weeks, and median response duration was 44 weeks. Simon-Makuch estimates for 52-week progression-free survival for patients progression-free at 13 weeks were 48% for response and 28% for nonresponse. When response was treated as a time-dependent covariate in a Cox proportional hazards regression analysis, response was associated with significantly lower failure rates (hazard ratio 0.5; 95% confidence interval 0.3-0.8; P = 0.0016). This study showed that response in recurrent glioma is associated with a significant reduction in progression rates.